High flow nasal cannula therapy versus standard oxygen therapy in bronchiolitis: a prospective randomized control trial - Herakal, Santosh U.; Indi, Shivakumar; Malagi, Naushad Ali N.; Thobbi, A. N. (International Journal of Contemporary Pediatrics, 2024)
Background: Bronchiolitis is most common respiratory infection in infants and treatment focuses on management of respiratory distress and hypoxia. The clinical effectiveness of HFNC therapy in bronchiolitis has been reported only in non-experimental observational studies and also there is scarcity of high-grade evidence about HFNC usage in bronchiolitis, hence we intend to study the effectiveness of HFNC in bronchiolitis through prospective randomized control study. Methods: It is prospective randomized control trial conducted at pediatric ward/ ICU at department of paediatrics, Al Ameen medical college, Bijapur from January 2023 to April 2024 all children diagnosed as bronchiolitis aged between 2 to 24 months were included. All of study participants had thorough histories obtained, including demographic information, vital parameters including SaO2 in room air. (Clinical severity score) by modified Wood’s clinical asthma score (M-WCAS) at admission and 2nd hourly till oxygen support is completely weaned off. Treatment failure is defined as meeting ≥3 out of 4 clinical criteria: persistent tachycardia, tachypnea, hypoxemia and decision of escalation by treating doctor. Primary outcome was treatment failure and need of escalation of therapy. Results: A total of 65 cases are randomized, among them 33 cases are allocated to standard oxygen therapy and 32 cases to high flow nasal cannula group. HFNC group showed lower proportion of treatment failure than standard oxygen therapy group (p<0.0005). Secondary outcomes are also compared with previous studies. Conclusions: HFNC group showed lower proportions of treatment failure than standard oxygen therapy.